2014
DOI: 10.1108/ijppm-06-2013-0120
|View full text |Cite
|
Sign up to set email alerts
|

Lean machine manufacturing at Munjal Showa limited

Abstract: Purpose – The global manufacturing industry is becoming more competitive. Munjal Showa, a shock absorber manufacturer in India, is using indigenous development of lean machines by incorporating concepts of lean manufacturing and low-cost automation techniques to increase their competitiveness. This new approach has helped the company to reduce cost of manufacturing and to increase productivity by reducing cycle time and down time. The purpose of this paper is to offer an in depth study of how a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In the present scenario, the management team prefers industry 4.0 techniques to enhance productivity by maintaining industrial sustainability within limited constraints. It has been observed that satisfactory results may not be obtained by applying the methodologies developed in the previous research works to other management systems [3,8,22,24,27,50,64,67,69,84]. erefore, in the present research work, such a management system has been developed that can be applied in all types of production conditions.…”
Section: Enhancement Of Industrial Sustainability Of the Developed Me...mentioning
confidence: 84%
“…In the present scenario, the management team prefers industry 4.0 techniques to enhance productivity by maintaining industrial sustainability within limited constraints. It has been observed that satisfactory results may not be obtained by applying the methodologies developed in the previous research works to other management systems [3,8,22,24,27,50,64,67,69,84]. erefore, in the present research work, such a management system has been developed that can be applied in all types of production conditions.…”
Section: Enhancement Of Industrial Sustainability Of the Developed Me...mentioning
confidence: 84%
“…Lean as an operational model for MSMEs in developing countries has gained momentum in the past decade [18]. Contemporary literature indicates similar trend with the extension of lean implementation to Indian small and medium enterprises.…”
Section: Themes Referencesmentioning
confidence: 94%
“…[ [16][17][18][19][20][21] Lean Performance includes articles that deliberate impact of lean on organizational performance [14,[22][23][24][25] Studies discussing lean status of an organization i.e. leanness [26][27][28][29] lean implementation in Indian Small and Medium enterprises.…”
Section: Themes Referencesmentioning
confidence: 99%
“…Singh et al [28] developed an approach to convert the cumbersome machine into a lean machine. The approach helped to reduce the cost of manufacturing and increased productivity by reducing cycle time and downtime.…”
Section: Process Optimization Approach Used In Operation Management O...mentioning
confidence: 99%